Some Euglenophycean Algae from Biratnagar, Nepal - Rai, SK; Rai, RK (Our Nature, 2008)
A total 19 euglenophycean taxa (Euglena 4, Phacus 8, Trachelomonas 5, Lepocinclis 2) has been reported from ponds, pools and ditches of Biratnagar in the present communication. Among these, nine taxa viz., Euglena sanguinea Ehrenberg, E. tripteris (Dujardin) Klebs, Phacus birgei Prescott, P. helikoides Pochmann, P. pleuronectes (Mueller) Dujardin, P. spirogyra Drezepolski var. maxima Prescott, Trachelomonas armata (Ehrenberg) Stein var. steinii Lemmermann, T. similis Stokes and Lepocinclis ovum (Ehrenberg) Lemmermann are being reported for the first time from Nepal. Keywords: Algae, Euglenophyceae, Phacus, Biratnagar, Nepal. doi:10.3126/on.v5i1.799 Our Nature (2007)5:60-66